Salt-Enrichment Impact on Biomass Production in a Natural Population of Peatland Dwelling Arcellinida and Euglyphida (Testate Amoebae) - Whittle, A; Amesbury, MJ; Charman, DJ; Hodgson, DA; Perren, BB; Roberts, SJ; Gallego-Sala, AV (Microbial Ecology, 2018)
This is the final version. Available on open access from Springer Verlag via the DOI in this record Unicellular free-living microbial eukaryotes of the order Arcellinida (Tubulinea; Amoebozoa) and Euglyphida (Cercozoa; SAR), commonly termed testate amoebae, colonise almost every freshwater ecosystem on Earth. Patterns in the distribution and productivity of these organisms are strongly linked to abiotic conditions—particularly moisture availability and temperature—however, the ecological impacts of changes in salinity remain poorly documented. Here, we examine how variable salt concentrations affect a natural community of Arcellinida and Euglyphida on a freshwater sub-Antarctic peatland. We principally report that deposition of wind-blown oceanic salt-spray aerosols onto the peatland surface corresponds to a strong reduction in biomass and to an alteration in the taxonomic composition of communities in favour of generalist taxa. Our results suggest novel applications of this response as a sensitive tool to monitor salinisation of coastal soils and to detect salinity changes within peatland palaeoclimate archives. Specifically, we suggest that these relationships could be used to reconstruct millennial scale variability in salt-spray deposition—a proxy for changes in wind-conditions—from sub-fossil communities of Arcellinida and Euglyphida preserved in exposed coastal peatlands. Natural Environment Research Council (NERC)